The Endovascular Armamentarium to Save the Dying Brain: Prospects and Challenges - Poyyamoli, Santhosh; Muddhan Prakash, Dilip Kumar; Ranasingh, Rahul Kareparambil; Mehta, Pankaj; Cherian, Mathew (Journal of Clinical Interventional Radiology ISVIR, 2017)
Purpose Acute ischemic stroke was not long ago the territory of the neurologist, where the endovascular surgeon had only started baby steps. The scenario has completely changed post-2015 and now mechanical thrombectomy holds centerstage of the treatment guidelines. The two basic techniques for clot retrieval are the stent retriever thrombectomy and a direct aspiration first-pass technique. Use of one device as an adjunct to the other also has a passing mention in the trials. Tandem occlusions pose issues in accessing the target vessel for clot retrieval, and emergency stenting of the carotid pathway opens further avenues in stroke care.Cases The authors present four cases of acute ischemic stroke, three of them involving the anterior circulation and one involving the basilar artery. All the cases underwent endovascular therapy, albeit with different techniques. Through the cases, they present the current technology, and its implementation and challenges faced by the interventional radiologist.Conclusion The availability of a diverse technical repertoire helps in tackling specific scenarios facing the stroke interventionist. The levels of evidence vary for the different weapons at hand, but it is not long before endovascular intervention becomes the panacea for stroke.
Keywords: acute ischemic stroke; endovascular therapy